2009
DOI: 10.1111/j.1365-263x.2009.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease in mothers indicates risk in their children

Abstract: Maternal indicators, such as periodontitis, hygiene habits, and periodontal microflora are risk factors for childhood periodontal diseases, and might be predictive of future childhood and adolescent periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…They also detected that 71% of children with a diseased mother had some alteration in gingiva (gingivitis or periodontitis), while only 15% of children of healthy mothers had these conditions (Pähkla et al. ). These results are similar to ours and suggest that the periodontal status of parents could explain the periodontal condition of their children.…”
Section: Discussionmentioning
confidence: 99%
“…They also detected that 71% of children with a diseased mother had some alteration in gingiva (gingivitis or periodontitis), while only 15% of children of healthy mothers had these conditions (Pähkla et al. ). These results are similar to ours and suggest that the periodontal status of parents could explain the periodontal condition of their children.…”
Section: Discussionmentioning
confidence: 99%
“…The poor gingival condition of mothers contributes to the severity of dental caries of their children. Periodontal bacteria of mothers can transmit between family members through daily activities [8,11,24]; Pähkla et al and Tamura et al have found periodontal bacteria in saliva samples of children to be strongly associated with that of their mothers [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Vertical transmission of periodontopathogens, usually from mother to child, has also been demonstrated, with children having strains of periodontopathogens from both parents . More children of mothers with periodontal disease showed clinical signs of gingival inflammation, including bleeding on probing and higher modified gingival index scores, compared with children whose mothers had healthy periodontal tissues (, ). Pathogenic bacteria, such as Prevotella intermedia/nigrescens and Aggregatibacter actinomycetemcomitans , were more likely to be isolated in these children.…”
Section: Dental Plaque Periodontal Disease and Dental Cariesmentioning
confidence: 99%